Ocorrência de parasitas gastrintestinais em cães e gatos na rotina do laboratório de enfermidades parasitárias da FMVZ/Unesp-Botucatu, SP. - Torrico, Keila J; Santos, Karina R; Martins, Thiago; Paz E Silva, Flavio M; Takahira, Regina Kiomi [UNESP]; Lopes, Raimundo Souza [UNESP] (My University, 2008)
With the object of determining the occurrence and prevalence of parasites in dogs and cats in the region of Botucatu, a survey was conducted from the results of fecal parasitologic exams feces, processed by the laboratory of parasitic diseases of FMVZ-UNESP/Botucatu from January 2002 to December 2006. 1,012 fecal samples of dogs and cats were evaluated by the technique of Willis Mollay and Faust. In dogs the higher incidence was found for Ancylostoma caninum eggs (38%). In cats, the oocysts of Isospora spp were present in 48.38% of positive samples.
Occurrence of gastrointestinal parasites in dogs and cats in the laboratory of routine of parasitic diseases FMVZ/Unesp-Botucatu, SP
Keywords: animal; Brazil; cat; dog; feces; gastrointestinal tract; parasitology; Animals; Cats; Dogs; Feces; Gastrointestinal Tract